Prevalence, natural history, and clinical outcome of mild to moderate ventriculomegaly - Sethna, Farah; Tennant, Peter W G; Rankin, Judith; C Robson, Stephen (Obstetrics and gynecology (New York. 1953), 2011)
To estimate the prevalence, associated anomalies, progression, and clinical outcome in fetuses diagnosed with mild to moderate ventriculomegaly at 18-24 weeks of pregnancy. This was a prospective population-based study from the North of England. Data were extracted from the U.K. Northern Congenital Abnormality Survey for cases identified during 1994-2008. Additional anomalies present were categorized according to European Surveillance of Congenital Anomalies guidelines. Differences between isolated and nonisolated ventriculomegaly were examined by either Fisher's exact test or Mann-Whitney U test. Changes in prevalence were examined by the χ² test for trend. There were 355 cases of confirmed mild to moderate ventriculomegaly in singleton pregnancies at 18-24 weeks of gestation among 454,080 registered births, giving a total prevalence of 7.8 per 10,000 registered births (95% confidence interval [CI] 7.0-8.7). The minimum rate of chromosomal anomaly and trisomy 21 (including cases karyotyped postnatally) in isolated cases (ie, in which no other structural anomaly was identified prenatally) was 10.2% (95% CI 6.1-16.0) and 4.5% (95% CI 2.0-8.7), respectively. Additional structural anomalies were identified prenatally in 43.1% of cases. Among isolated cases, 61.9% (95% CI 53.3-70.0) resolved by the final prenatal scan (the majority by 24 weeks of gestation) and 10.7% (95% CI 6.4-16.6) were found to have "missed" structural anomalies after birth. The probability of an infant death for isolated ventriculomegaly was 3% (95% CI 0.8-7.6). This register-based study on mild to moderate ventriculomegaly provides unique epidemiologic and outcome data. Information from this study should aid in counseling parents. III.